Myeloid cells in alcoholic liver diseases: Mechanism and prospect - Xu, Wentao; Wu, Miaomiao; Chen, Bangjie; Wang, Hua (Frontiers in Immunology, 2022)
Alcoholic liver disease (ALD) is one of the leading chronic liver diseases, and immune cells play a vital role in the middle. Myeloid cells have been extensively studied in ALD, including granulocytes, macrophages, monocytes and dendritic cells, which are involved in the occurrence and progression of steatosis, inflammation, fibrosis and cirrhosis eventually. These cells can be targeted and regulated by factors from different sources, including cytokines secreted by other cells, extracellular vesicles, substances in serum, which in turn affect changes in their function and phenotype. For example, infiltration of monocytes or neutrophils, activation of kupffer cells (KCs), polarization of macrophages. Here, we mainly review the key mediators that affect the infiltration and function of mainly myeloid cells in ALD, as well as their regulatory mechanisms on target cells, which may provide novel immunotherapeutic approaches. The single-cell multimodal omics of myeloid cells is also discussed, helping transform them into therapeutic strategy or basic research of ALD clinically. Keywords: alcoholic liver diseases, immunity, myeloid cells, cell-cell communication, single-cell multimodal omics.